Java programming basics for the Internet : for use with microsoft Visual J++ ver .1.1 - Turner, E. Shane.; Barksdale, Karl.; Ashton, Gary. (South-Western Educational, 1998)
Java rides the Web. Building Java applets with visual J++. Applets on the superhighway.